2016
DOI: 10.1089/neu.2014.3424
|View full text |Cite
|
Sign up to set email alerts
|

Concussion History in Adolescent Athletes with Attention-Deficit Hyperactivity Disorder

Abstract: Little is known about the rate of concussions in adolescents with attention-deficit hyperactivity disorder (ADHD). We hypothesized that high school athletes with ADHD would report a greater history of concussion than students without ADHD. A total of 6529 adolescent and young adult student athletes, between the ages of 13 and 19 years (mean, 15.9; standard deviation, 1.3), completed a preseason health survey in 2010. Of those with ADHD, 26.1% reported a history of one or more concussions, compared to 17.1% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 22 publications
2
54
1
Order By: Relevance
“…Workers who reported a history of mTBI on both the screener and OSU TBI-ID were more likely to have been diagnosed with depression, anxiety, and ADHD than workers who did not endorse a history of mTBI on either measure; also, workers who reported a history of mTBI on the OSU TBI-ID but denied any history on the screener were more likely to have been diagnosed with depression and anxiety than those who did not endorse mTBI history on either measure. Individuals with a history of mTBI are at greater risk of developing each of these disorders after injury [37,38,47]. However, whereas previous non-MTurk studies reported an average elapsed time of between 1 and 18 months between injury and diagnosis of a disorder, the current study identified a considerably longer period (ie, between 3 and 7 years after injury).…”
Section: Comorbid Diagnoses and Current Symptoms Comparisonscontrasting
confidence: 68%
See 1 more Smart Citation
“…Workers who reported a history of mTBI on both the screener and OSU TBI-ID were more likely to have been diagnosed with depression, anxiety, and ADHD than workers who did not endorse a history of mTBI on either measure; also, workers who reported a history of mTBI on the OSU TBI-ID but denied any history on the screener were more likely to have been diagnosed with depression and anxiety than those who did not endorse mTBI history on either measure. Individuals with a history of mTBI are at greater risk of developing each of these disorders after injury [37,38,47]. However, whereas previous non-MTurk studies reported an average elapsed time of between 1 and 18 months between injury and diagnosis of a disorder, the current study identified a considerably longer period (ie, between 3 and 7 years after injury).…”
Section: Comorbid Diagnoses and Current Symptoms Comparisonscontrasting
confidence: 68%
“…The current study used the 6-item questionnaires for depression, anxiety, sleep problems, and cognitive complaints [36]. Specific mental illnesses and conditions were included based on their established comorbidity with mTBI [37,38].…”
Section: Mental Health Historymentioning
confidence: 99%
“…53 In addition, previous retrospective work has demonstrated that children with ADHD and collegiate athletes with ADHD are more likely to self-report a history of concussion. 54,55 However, the fact that the effect sizes were generally equivalent for analyses with and without athletes with self-reported ADHD suggests that the observed differences in cortical thickness were not principally driven by ADHD. However, the interaction between ADHD, cortical thickness, and concussion history requires future investigation in larger sample sizes.…”
Section: Discussionmentioning
confidence: 97%
“…Pre-morbid learning disorders, behavioural issues, or mental health problems are all known to be the source of a number of the post-concussion symptoms and clusters of symptoms [37]. For example, athletes with Attention Deficit Hyperactivity Disorder (ADHD) [38][39][40][41][42] or learning problems [39] have a greater lifetime history of concussion, and individuals with a prior history are at increased risk for a future concussion [43].…”
Section: Clinical Historymentioning
confidence: 99%